Adopting an enterprise resource planning system in a privatized government unit: challenges and impacts - Zainol, Zaini; Hamdan, Hamdino (Kolej Universiti Poly-Tech MARA Kuala Lumpur, 2015)
There are many studies on Enterprise Resource Planning (ERP) systems available in the academic journals. However, the studies are more quantitative than qualitative. By adopting the qualitative approach, this study investigates how an ERP system is implemented in one of government privatized units and its implication. The study focuses on the implementation issues and impact of ERP adoption on operational and labour productivity. A series of interviews was conducted with one of the top management in-charged on corporate affairs of the company. Findings from the study revealed that, the implementation of its ERP system specifically Pronto received mixed response from employees. The older employees who opted to remain with the new company were found to be resistance towards Pronto system. Other challenges face by the company during the implementation were also highlighted. In terms of labour productivity, the study found that post three years of ERP adoption had shown the labour productivity increased by 37.7 percent. Pronto has also brought lots of benefit to the company operationally. These benefits were discussed further in the paper.